PREVALENCE AND PHENOTYPIC DETECTION OF BETA-LACTAMASES IN CLINICAL ISOLATES OF GRAM-NEGATIVE BACTERIA FROM SOUTHWESTERN NIGERIA - Mensah-Agyei, Grace Oluwatoyin; Nasiru, Bright Lecky; Akeredolu, Abosede Abolanle; Ogunbiyi, Opeyemi Christiana; Ofem, Oluchi Gladys; Adeleke, Olufemi Ezekiel (FUDMA Journal of Sciences, 2026)
Antimicrobial resistance among Gram-negative bacteria represents a major public health challenge globally, with extended-spectrum β-lactamase (ESBL) and metallo-β-lactamase (MBL) production significantly limiting therapeutic options. In Nigeria, increasing resistance to β-lactam antibiotics has been reported, yet comprehensive phenotypic data across multiple tertiary healthcare facilities remain limited. This study determined the prevalence and phenotypic detection of ESBL- and MBL-producing Gram-negative bacteria isolated from clinical specimens in southwestern Nigeria. A total of 285 non-duplicate Gram-negative bacterial isolates were collected between August 2021 and April 2023 from urine, wound swabs, stool, sputum, and blood samples across three tertiary hospitals. Isolates were identified using standard microbiological and biochemical methods. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disc diffusion method. Isolates exhibiting resistance or reduced susceptibility to third-generation cephalosporins were screened phenotypically for ESBL and MBL production using the double-disk synergy and combination disk tests. The isolates demonstrated extremely high resistance to β-lactam antibiotics, particularly third-generation cephalosporins. Resistance rates exceeded 85% for cefotaxime, cefixime, cefuroxime, and ceftriaxone-sulbactam among Klebsiella and Escherichia coli isolates. High resistance was also observed against β-lactam/β-lactamase inhibitor combinations and carbapenems. Phenotypic assays confirmed a high prevalence of ESBL producers, with the additional detection of MBL activity in a subset of isolates, indicating the emergence of carbapenem resistance. The high prevalence of ESBL- and MBL-producing Gram-negative bacteria in southwestern Nigeria poses a serious threat to effective antimicrobial therapy. Routine resistance surveillance, strengthened antimicrobial stewardship, and improved diagnostic capacity are urgently needed to curb the spread of these multidrug-resistant pathogens.
Keywords: Antimicrobial resistance; Extended-spectrum β-lactamase; Metallo-β-lactamase; Gram-negative bacteria; Nigeria